توظيف تقنيات الذكاء الاصطناعي في الدعوة الى الله: دراسة تحليلية وتطبيقية: Employing Artificial Intelligence Technologies in “Calling to God”: An Analytical and Applied Study - Abddulla M.A. Al-Marri, AbdulRahman (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث تهدف هذه الدراسة إلى بحث إمكانيات توظيف الذكاء الاصطناعي في مجال الدعوة الإسلامية، مع التركيز على آليات الرد على الشبهات والاستفسارات. تكمن مشكلة البحث في تحديد الأساليب المثلى لاستخدام التقنيات الذكية في نشر الدعوة مع الحفاظ على أصالتها وضوابطها الشرعية. اعتمد البحث المنهج الاستقرائي التحليلي في دراسة التطبيقات الممكنة للذكاء الاصطناعي في المجال الدعوي. وتوصلت الدراسة إلى فعالية استخدام تقنيات الذكاء الاصطناعي في تطوير العمل الدعوي من خلال أنظمة الحوار الآلي. Abstract This study aims to explore the possibilities of utilizing artificial intelligence (AI) in the field of Islamic da’wah (propagation), with a focus on mechanisms for responding to misconceptions and inquiries. The research problem lies in identifying the optimal methods for employing intelligent technologies to spread Islamic teachings while maintaining their authenticity and adherence to Sharia principles. The study adopted an inductive analytical methodology to examine the potential applications of AI in the da’wah field. The findings indicate the effectiveness of using AI technologies in enhancing da’wah activities through automated dialogue systems.